PERKEMBANGAN HUKUM ISLAM (Kodifikasi dan Unifikasi) - Djaenab Djaenab (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2019)
This article outlines the development of Islamic law in Indonesia with a historical juridical approach. From the results of the discussion it can be understood that in the course of history the development of Islamic law in Indonesia is closely related to the government's attitude towards the nature of Islamic law. Misunderstandings about the nature of Islamic law may cause them to be antipathic and even hostile to Islamic law. To solve this problem, the scholars, Muslim scholars, Muslim politicians need to cooperate well to convince the Indonesian government and the non-Islamic community that Islamic law is universal and flexible. The codification and unification of Islamic law into the national legal system should not be enough to just stop the issuance of laws on marriage and religious justice, zakat, endowments only, but there still needs to be other aspects of Islamic law that need to be codified and verified, for example on Islamic economics. siyasah, jinayah and various other aspects of Islamic law.